Efektivitas Expressive Writing Therapy dalam Meningkatkan Self-Efficacy pada Siswa Kelas XII - Nawzha Junaedi Airadhika; Daffa Ahmad Naufal; Abdul Rosyid; Aisyah Puspitasari (Pusat riset dan Inovasi Nasional, 2024)
Adolescence is a crucial period where individuals begin to build their self-identity in determining the direction of their lives, especially in grade XII students. Where this condition often causes anxiety, self-doubt, feelings of boredom, and social pressure, one important aspect that influences an individual's ability to adapt and resilience to these challenges is self-efficacy. Someone with high self-efficacy is usually more optimistic, resilient, and able to overcome challenges to achieve their goals. The purpose of this study was to determine the effectiveness of expressive writing techniques in improving self-efficacy. Participants in this study were 34 students, who were divided into two groups, namely the control group and the experimental group. The experimental group was given treatment in the form of expressive writing. This study used a Quasi-Experimental research type with a Two-Group Pretest-Posttest Design. Data analysis used in this study was processed using Jamovi software. While the data analysis method used was the paired test and independent sample T-Test. Based on the results of the analysis of the pretest and posttest scores of the experimental group, a significant value of 0.280 (p> 0.05) was shown, which means there was no significant difference in the level of students' self-efficacy after treatment. Thus, it can be concluded that expressive writing treatment can improve students' self-efficacy.